Effect and safety of ethanolamine oleate in sclerotherapy in patients with difficult-to-resect venous malformations: A multicenter, single-arm study - Mine Ozaki; Tadashi Nomura; Keigo Osuga; Masakazu Kurita; Ayato Hayashi; Shunsuke Yuzuriha; Noriko Aramaki-Hattori; Makoto Hikosaka; Taiki Nozaki; Michio Ozeki; Junko Ochi; Shimpei Akiyama; et al. (PLoS ONE, 2025)
Objective To evaluate the effect and safety of sclerotherapy in patients with difficult-to-resect venous malformations treated with ethanolamine oleate. Design and setting This investigator-initiated clinical trial employed a multicenter, single-arm design and was conducted in Japan. Patients Overall, 44 patients with difficult-to-resect venous malformations were categorized into two cohorts: 22 patients with cystic-type malformations and 22 patients with diffuse-type malformations, including children (<15 years old). Interventions Adult patients received injections of 5% ethanolamine oleate solution, double diluted with contrast or normal saline, with a maximum dose of 0.4 mL/kg. The same method of administration was used for children (<15 years old). The maximum volume of the prepared solution in one treatment was 30 mL. Evaluation methods Treatment effect was assessed by evaluating the difference in lesion volume using magnetic resonance imaging as a primary endpoint and differences in pain using a visual analog scale as a key secondary endpoint. Results Among the 45 patients who consented, one was excluded owing to potential intracranial involvement of venous malformations during screening. Regarding the primary outcome, 26 of 44 patients (59.1%, 95% confidence interval: 44.41–72.31%) achieved ≥ 20% reduction in malformation volume, with 16 patients having cystic lesions (72.7%, 51.85–86.85%) and 10 patients having diffuse lesions (45.5%, 26.92–65.34%). Both cohorts showed significant improvement in self-reported pain scores associated with lesions 3 months post-sclerotherapy. No death or serious adverse events occurred. Hemoglobinuria was observed in 23 patients (52%), a known drug-related adverse event. Prompt initiation of haptoglobin therapy led to full recovery within a month for these patients. Conclusions Ethanolamine oleate shows potential as a therapeutic sclerosing agent for patients with difficult-to-resect venous malformations.